A stabilized node-based smoothed radial point interpolation method for functionally graded magneto-electro-elastic structures in thermal environment. (15th February 2020) - Ren, Shuhui; Meng, Guangwei; Wang, Jiye; Zhou, Liming; Zhao, Hongwei
Abstract: It is well-known that the standard finite element method (FEM) has the disadvantage of 'overly-stiff' and could not offer reliable enough solutions. We proposed a novel stabilized node-based smoothed radial point interpolation method (SNS-RPIM) to analyze the free vibration and the behavior of functionally graded magneto-electro-elastic (FGMEE) devices under mechanical and thermal load, which cured the 'overly-soft' and temporally instability of traditional NS-RPIM. The gradient variance items associated with the field nodes are applied to construct the system stiffness matrix. The detailed numerical study has shown the superiority of the proposed method. SNS-RPIM performs well in solving static magneto-electro-thermo-elastic (METE) multi-physics coupling field problems, which validates the accuracy, convergence of the proposed method. Moreover, SNS-RPIM is less insensitive to mesh distortion than FEM and NS-RPIM. The advantages mentioned above make SNS-RPIM very helpful for the design of the actual intelligent devices.